A kind of waste foam CA mortar grouting material and its preparation method and application
By using waste foam CA mortar grouting materials prepared by using waste foam particles and other raw materials, the existing light embankment grouting materials have solved the problem of low flow, high cost and difficulty in meeting strength and thermal insulation properties at the same time, and achieved higher flow , strength and low thermal conductivity effects are suitable for the restoration of road infrastructure.
Patent Information
- Application Number
- CN202310698449.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-06-13
AI Technical Summary
The existing lightweight embankment grouting materials have low flow, high cost, and are difficult to meet the needs of strength and thermal insulation.
Waste foam CA mortar grouting materials are prepared through specific ratios and stirring processes by using waste foam particles, cationic emulsified asphalt, cement, fine sand, low thermal conductivity materials.
The prepared grouting material has higher flow, strength and low thermal conductivity, which can effectively fill voids and discontinuous disease areas in road infrastructure, reduce self-weight and reduce thermal conductivity, and is suitable for road restoration in high altitude and high cold areas. .
Smart Images

Figure BDA0004282775790000051 
Figure BDA0004282775790000061 
Figure BDA0004282775790000062
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of road maintenance and reinforcement materials, and specifically relates to a waste foam CA mortar grouting material and a preparation method and application thereof. Background Art
[0002] As the operation time of road traffic infrastructure increases, there will be a discontinuous state of emptying between road structure layers, behind retaining walls, and in tunnel linings. For these diseases, if grouting materials are used to pour into these diseased areas with a certain pressure without destroying the current facilities, the rapid repair of traffic infrastructure will be achieved, which will significantly improve the service level and quality of the facilities and save investment. In recent years, a large number of lightweight embankments have been used. They are made of fly ash, expanded polystyrene, etc., which have the advantages of reducing the deadweight of embankments, reducing soft soil settlement, improving soil shear strength, and reducing land occupation. However, the price of expanded polystyrene is relatively high, and the fluidity of the obtained grouting material is relatively low. The strength and thermal insulation performance of the formed lightweight embankment cannot meet the requirements at the same time. Therefore, how to reduce the cost of lightweight embankment grouting materials while obtaining a grouting material with higher fluidity, higher strength and better thermal insulation performance is a technical problem that needs to be solved in this field. Summary of the invention
[0003] In order to solve the above problems in the prior art, the present invention provides a waste foam CA mortar grouting material and a preparation method and application thereof, and the prepared grouting material is used to fill the voids and discontinuous diseased areas in the transportation infrastructure to make the structure continuous, reduce the dead weight while reducing the thermal conductivity, and also meet the corresponding strength requirements.
[0004] To achieve the above object, the present invention provides the following technical solutions:
[0005] The invention provides a waste foam CA mortar grouting material. The raw materials include, by weight, 250-300 parts of cationic emulsified asphalt, 300-400 parts of cement, 200-800 parts of fine sand, 1-3 parts of waste foam particles, 180-220 parts of water, 3-5 parts of water reducer, 0.5-1 part of defoamer, and 5-10 parts of low thermal conductivity material; the thermal conductivity of the low thermal conductivity material is 0.01-0.07 W / (m·K).
[0006] As a preferred embodiment of the present invention, the cationic emulsified asphalt has an Engla viscosity of 2-30 at 25°C, an evaporation residue content of 50% to 65wt%, and a storage stability of no more than 1% and 5% at 1d and 5d, respectively.
[0007] As a preferred embodiment of the present invention, the waste foam particles are obtained by crushing waste polystyrene foam (EPS) used to prepare exterior wall insulation materials or express packaging foam (mainly composed of EPS).
[0008] As a preferred embodiment of the present invention, the low thermal conductivity material is selected from one or more of expanded perlite, glass microspheres, silica aerogel, expanded vermiculite powder, aluminum silicate, diatomaceous earth and calcium carbonate whiskers.
[0009] As a preferred embodiment of the present invention, the initial setting time of the cement is not less than 45 minutes, and the final setting time is not more than 600 minutes.
[0010] As a preferred embodiment of the present invention, the fineness modulus of the fine sand is 2.2-1.6, the average particle size is 0.075mm-0.125mm, and the sand equivalent value is not less than 60% according to the "Highway Engineering Aggregate Test Code" (JTGE42-2005).
[0011] As a preferred embodiment of the present invention, the water reducer is a high-efficiency water reducer with a water reduction rate of not less than 14%, including one or more of naphthalene series, melamine series, polycarboxylic acid, aminosulfonate series and aliphatic series; the defoamer is a polyether modified polysiloxane defoamer.
[0012] The present invention also provides a method for preparing the above-mentioned waste foam CA mortar grouting material, comprising the following steps:
[0013] (1) Weighing each raw material according to its mass fraction, mixing fine sand, cement and waste foam particles in a mixer with orbiting and rotating motions;
[0014] (2) adding water to the mixture obtained in step (1) and continuing stirring;
[0015] (3) Add cationic emulsified asphalt, a water reducing agent, a defoaming agent and a low thermal conductivity material to the mixture obtained in step (2), and stir to obtain the waste foam CA mortar grouting material.
[0016] As a preferred embodiment of the present invention, in step (1), the stirring speed is 105±5 r / min of revolution and 40±10 r / min of rotation, and the time is 20 to 40 s; in step (2), the stirring speed is 105±5 r / min of revolution and 40±10 r / min of rotation, and the time is 10 to 20 s; in step (3), the stirring is specifically as follows: first, stirring at a speed of 140±5 r / min of revolution and 62±5 r / min of rotation for 50 to 70 s, standing for 10 to 20 s, and then stirring at a speed of 285±10 r / min of revolution and 125±10 r / min of rotation for 40 to 50 s.
[0017] The present invention also provides the use of the above-mentioned waste foam CA mortar grouting material in the repair of hollowing out between road structure layers, behind retaining walls or in tunnel linings, especially in the repair of hollowing out between road structure layers, behind retaining walls or in tunnel linings in high-altitude and cold areas.
[0018] As a preferred embodiment of the present invention, the high altitude area is Zone VII specified in the "Highway Natural Zoning Standard" (JTJ003-86), namely the Qinghai-Tibet high-altitude cold area; the high-altitude cold area is Zone I specified in the "Highway Natural Zoning Standard" (JTJ003-86), namely the northern permafrost area.
[0019] Technical concept of the present invention:
[0020] The present invention utilizes waste foam particles, adds a binder and a low thermal conductivity material, and prepares a lightweight grouting material with a certain fluidity, strength and low thermal conductivity, which is poured into the damaged parts of the road traffic infrastructure to play a reinforcing role and make up for the deficiencies of the prior art.
[0021] The present invention serves road traffic infrastructure that has been in operation for a period of time, which is significantly different from newly built lightweight embankments or corresponding materials. On the one hand, since it needs to be poured into the diseased part, the grouting material needs to have a certain degree of fluidity. On the other hand, the poured material cannot be rolled or compacted, and the material strength formation mechanism is also different from the new construction method. Finally, in order to improve the thermal insulation performance, the thermal conductivity should be reduced as much as possible, so it is necessary to balance the relationship between thermal conductivity and strength.
[0022] Therefore, the present invention provides a waste foam CA mortar grouting material and a preparation method thereof. The prepared grouting material meets the strength requirements while reducing its own weight and thus reducing the settlement, and reducing the thermal conductivity to protect the roadbed from frost damage, which is of great significance especially in high altitude and cold regions.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The present invention provides a waste foam CA mortar grouting material and a preparation method thereof. The raw materials include waste foam particles, which realizes the green application of bulk solid waste materials in road maintenance projects and reduces environmental pressure.
[0025] (2) The grouting material prepared by the technical solution of the present invention has the characteristics of good fluidity (can fully fill discontinuities), light weight (effectively prevent further expansion of invisible diseases such as settlement and slope sliding), low thermal conductivity (reduces heat exchange between the structure and the environment and improves service performance), and high strength (the bonding material forms the required strength when the optimal ratio is reached).
[0026] (3) The waste foam CA mortar grouting material of the present invention can be widely used in special engineering parts that need to reduce dead weight, reduce heat transfer, and have sufficient strength and rigidity. For example, it can be widely used in the grouting filling of road surface voids in seasonally frozen areas, the reinforcement of road voids, bridge head jumping, voids behind retaining walls, tunnel lining cavities and other invisible diseases, and the antifreeze layer in high-cold and high-altitude areas. DETAILED DESCRIPTION
[0027] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0028] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0029] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0030] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0031] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0032] Unless otherwise specified, the "parts" described in the present invention are all based on mass parts.
[0033] In the following embodiments and comparative examples, CA mortar refers to the abbreviation of cement asphalt mortar well known in the art.
[0034] In the following embodiments, the cement used was purchased from Henan Mengdian Group, with an initial setting time of 60 min and a final setting time of 480 min; the fineness modulus of the fine sand used was 1.9, the average particle size was 0.125 mm, and the sand equivalent value was 63%; the waste foam particles used were purchased from Henan Xinsheng Building Energy Saving Decoration Co., Ltd., with a component composition of EPS and a particle size range of 3-4 mm; the cationic emulsified asphalt used was cationic emulsified asphalt for roads, purchased from Henan Weisend Road Materials Co., Ltd., with an Engela viscosity of 15 at 25°C, an evaporation residue content of 62wt%, and storage stability of 0.5% and 2.3% at 1d and 5d, respectively; the water reducer used was a polycarboxylic acid high-efficiency water reducer purchased from Zhaojia Technology, with a water reduction rate of 17 %; the defoaming agent used is a polyether modified polysiloxane defoaming agent purchased from Henan Guanliang Chemical Co., Ltd.; the expanded perlite, glass beads and expanded vermiculite powder used were purchased from Xinyang Mingda Mineral Products Co., Ltd., with thermal conductivity of 0.05W / (m·K), 0.053W / (m·K) and 0.06W / (m·K), calcium carbonate whiskers were purchased from Hebei Senade Nanomaterial Technology Co., Ltd., with thermal conductivity of 0.05W / (m·K), aluminum silicate and diatomaceous earth were purchased from Hubei Keward Chemical Co., Ltd., with thermal conductivity of 0.07W / (m·K) and 0.0158W / (m·K), and silica aerogel was purchased from Henan Ruibo Environmental Engineering Technology Co., Ltd., with thermal conductivity of 0.013-0.016W / (m·K).
[0035] Examples 1 to 12
[0036] The waste foam CA mortar grouting material was prepared using the raw materials in Table 1:
[0037] Table 1
[0038]
[0039] The preparation steps of waste foam CA mortar grouting materials are as follows:
[0040] According to the material ratios of Examples 1 to 12 above, fine sand, cement and waste foam particles are added to a stirring pot with revolving and rotating stirring blades, and stirred for 30 seconds at a speed of 100 r / min of revolution and 40 r / min of rotation; water is added and stirring is continued for 15 seconds at a speed of 100 r / min of revolution and 40 r / min of rotation, and then cationic emulsified asphalt, water reducer, defoaming agent and low thermal conductivity material are added, and the stirring speed is increased to a speed of 140 r / min of revolution and 62 r / min of rotation, and stirred for 60 seconds. After waiting for 15 seconds, the stirring speed is increased to a speed of 285 r / min of revolution and 125 r / min of rotation, and stirred for 45 seconds. When the stirring is completed, the grouting material is obtained.
[0041] The fluidity of the grouting materials prepared in Examples 1 to 12 is shown in Table 2.
[0042] After the grouting materials prepared in Examples 1 to 12 were made into test specimens required by the "Highway Geotechnical Test Code" (JTG 3430-2020), the dry density, thermal conductivity, 28d unconfined compressive strength and California bearing ratio (CBR) after molding were tested. The results are shown in Table 2. The 28d unconfined compressive strength and CBR must meet the requirements of the "Technical Specifications for Highway Roadbed Construction" (JTG / T3610-2019).
[0043] Table 2
[0044]
[0045] It can be seen from Table 2 that the construction fluidity of the grouting material is controlled at 150-200 mm. After the grouting material is made into a test piece required by the specification, the 28d unconfined compressive strength and California bearing ratio (CBR) are not less than 1.0 MPa and 8% respectively, meeting the requirements of the current "Technical Specifications for Highway Roadbed Construction" (JTG / T 3610-2019). The dry density of the grouting material after molding is 400-500 kg / m 3 The thermal conductivity of the grouting material is not greater than 0.12W / (m·K). The thermal insulation material in the building generally refers to the material with a thermal conductivity ≤0.12W / (m·K).
[0046] Comparative Examples 1-2
[0047] The raw materials in Table 3 are used to prepare conventional grouting materials:
[0048] Table 3
[0049]
[0050] Among them, the silicate cement is the same as the silicate cement used in Example 1, the geopolymer is purchased from Henan Nuoji Building Materials Co., Ltd., and the latex is purchased from Henan Weisend Road Materials Co., Ltd.
[0051] The preparation steps are as follows: according to the material ratios of Comparative Examples 1 and 2, water and latex are added to a stirring pot, and then silicate cement or geopolymer is added, and the grouting material is prepared by stirring for 180 seconds at a speed of 140 r / min and 62 r / min.
[0052] The performance test was carried out in the same manner as above, and the results are shown in Table 4.
[0053] Table 4
[0054]
[0055] It can be seen from Table 2 and Table 4 that, except for the strength being higher than that proposed in the present invention and the fluidity being equivalent to that proposed in the present invention, the other three indicators of the conventional grouting material are lower than those proposed in the present invention. Therefore, the comprehensive performance of the present invention is incomparable to that of the comparative example.
[0056] Comparative Examples 3 to 7
[0057] The amount of materials used is the same as that in Example 1, and the material composition is changed to form Comparative Examples 3 to 7, as shown in Table 5.
[0058] Table 5
[0059]
[0060] The performance test was carried out in the same manner as above, and the results are shown in Table 6.
[0061] Table 6
[0062]
[0063] It can be seen from Tables 5 and 6 that the excessive viscosity of emulsified asphalt, unclean fine sand (low sand equivalent), water reducer, defoamer, and thermal conductivity material affect the distribution uniformity of emulsified asphalt in the grouting material, the strength of the grouting material, fluidity, strength and comprehensive performance, especially the small particle size of the thermal conductivity material has better dispersion performance, which improves the uniformity and strength, which cannot be achieved through simple material mixing.
[0064] Comparative Examples 8 to 9
[0065] The material composition is the same as that in Example 1. When preparing the grouting material, the order of adding the materials and the stirring speed are changed, as shown in Table 7.
[0066] Table 7
[0067]
[0068] The performance test was carried out in the same manner as above, and the results are shown in Table 8.
[0069] Table 8
[0070]
[0071] The above description is only a preferred specific implementation manner of the present invention, and the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, and they should be covered by the protection scope of the present invention.
Claims
1. A waste foam CA mortar grouting material, characterized in that: The raw materials include, by weight: 250-300 parts of cationic emulsified asphalt, 300-400 parts of cement, 200-800 parts of fine sand, 1-3 parts of waste foam particles, 180-220 parts of water, 3-5 parts of water reducer, 0.5-1 part of defoamer, and 5-10 parts of low thermal conductivity material; the thermal conductivity of the low thermal conductivity material is 0.01-0.07 W / (m·K); The cationic emulsified asphalt has an Engela viscosity of 2-30 at 25°C, an evaporation residue content of 50% to 65wt%, and a storage stability of no more than 1% and 5% at 1d and 5d, respectively; the low thermal conductivity material is selected from one or more of expanded perlite, glass microspheres, silica aerogel, expanded vermiculite powder, aluminum silicate, diatomaceous earth and calcium carbonate whiskers; the fineness modulus of the fine sand is 2.2 to 1.6, the average particle size is 0.075mm to 0.125mm, and the sand equivalent value is not less than 60%; The preparation method of the waste foam CA mortar grouting material comprises the following steps: (1) Weighing each raw material according to the mass fraction, mixing fine sand, cement and waste foam particles in a mixer with orbital and autorotating functions; (2) adding water to the mixture obtained in step (1) and continuing stirring; (3) adding cationic emulsified asphalt, a water reducing agent, a defoaming agent and a low thermal conductivity material to the mixture obtained in step (2), and stirring to obtain the waste foam CA mortar grouting material; In step (1), the stirring speed is 105±5r / min for revolution and 40±10r / min for rotation, and the time is 20 to 40s; in step (2), the stirring speed is 105±5r / min for revolution and 40±10r / min for rotation. 10r / min, time is 10-20s; in step (3), first stir at a revolution speed of 140±5r / min and a rotation speed of 62±5r / min for 50-70s, let it stand for 10-20s, and then stir at a revolution speed of 285±10r / min and a rotation speed of 125±10r / min for 40-50s.
2. The waste foam CA mortar grouting material according to claim 1, characterized in that: The waste foam particles are obtained by crushing waste polystyrene foam used to prepare exterior wall insulation materials or express packaging foam.
3. The waste foam CA mortar grouting material according to claim 1, characterized in that: The initial setting time of the cement is not less than 45 minutes, and the final setting time is not more than 600 minutes.
4. The waste foam CA mortar grouting material according to claim 1, characterized in that: The water reducer is a high-efficiency water reducer with a water reduction rate of not less than 14%, including one or more of naphthalene series, melamine series, polycarboxylic acid, aminosulfonate series and aliphatic series; the defoamer is a polyether modified polysiloxane defoamer.
5. Use of the waste foam CA mortar grouting material according to any one of claims 1 to 4 in repairing voids between road structure layers, behind retaining walls or in tunnel linings.
Citation Information
Patent Citations
Preparation method of light-weight thermal mortar
CN103601454A
CA mortar material with high anti-freezing and shock sucking function
CN1821155A